Fire increases the risk of higher soil N2O emissions from Mediterranean Macchia ecosystems. (March 2015) - Karhu, K.; Dannenmann, M.; Kitzler, B.; Díaz-Pinés, E.; Tejedor, J.; Ramírez, D.A.; Parra, A.; Resco de Dios, V.; Moreno, J.M.; Rubio, A.; Guimaraes-Povoas, L.; Zechmeister-Boltenstern, S.; et al.
Abstract: Intensification of droughts under climate change is projected to increase fire frequency in the Mediterranean region. Fires cause direct emission of greenhouse gases (GHG) such as carbon dioxide (CO2 ) and nitrous oxide (N2 O), due to the combustion of organic matter, creating a positive feedback on climate change. However, the potential importance of indirect GHG emissions due to changes in soil biological and chemical properties after fire is less well known. Increased soil mineral nitrogen (N) concentrations after fire pose a risk for increased emissions of gaseous N, but studies on the post-fire N2 O production and soil N turnover rates (mineralization, nitrification, microbial immobilization, denitrification) are still rare. We determined N2 O production, rates of N turnover and pathways for N2 O production from the soil of burned and unburned plots of a Macchia shrubland in central Spain using a 15 N labelling approach. Measurements were initiated before the controlled burning and continued for up to half a year after fire. Fire markedly increased the risk of N2 O emissions from soil through denitrification (N2 O production rate was 3 to ≈30 times higher in burned soils compared to control, with N2 O being produced solely from soil nitrate). In contrast, soil gross N cycling rates were not accelerated after fire. Thus, the increased N2 O production was not closely linked with N mineralization, but may be explained by increased mineral N availability from ash, increased pH in burned plots, and less competition for available N and C sources due to absence of plants. Highlights: Fire increases the risk of N2 O emissions from Mediterranean Macchia ecosystems. Post-fire N2 O production was related to increased mineral N concentrations and pH. N2 O production rates not intimately linked with rates of biological N mineralisation. Post-fire effects on N2 O emissions decrease with time since fire.